ACTIVATION OF STUDENTS' COGNITIVE ACTIVITY IN THE SYSTEM OF LANGUAGE AND LITERARY EDUCATION THROUGH THE PRISM OF DISTANCE LEARNING - Lazarovych, Olga; Martynets, Alla (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article is devoted to the problem of education, in particular, to the activation forms during distance learning of students. Purpose of the article. The purpose of the study was to analyze the challenges that a teacher faces during distance learning in the implementation of language and literature education, and to search for forms of work aimed at activating the cognitive activity of students. Research methodology. The study used elements of the methods of source analysis, analysis and synthesis, classification and gene-ralization. Results. During the work, it was established that distance learning during crisis situations is an effective form of work, but it is associated with challenges of socialization, independence, and communication, which can be corrected using effective forms of work. Scientific novelty is seen in expan-ding the possibilities of language and literature education, which takes place in a distance learning format. Practical significance. The results obtained can be used during the preparation and conduct of language and literature classes in a distance form of work with students.